2016
DOI: 10.1038/ncomms10501
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive resistance to therapeutic PD-1 blockade is associated with upregulation of alternative immune checkpoints

Abstract: Despite compelling antitumour activity of antibodies targeting the programmed death 1 (PD-1): programmed death ligand 1 (PD-L1) immune checkpoint in lung cancer, resistance to these therapies has increasingly been observed. In this study, to elucidate mechanisms of adaptive resistance, we analyse the tumour immune microenvironment in the context of anti-PD-1 therapy in two fully immunocompetent mouse models of lung adenocarcinoma. In tumours progressing following response to anti-PD-1 therapy, we observe upreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
929
3
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,237 publications
(1,029 citation statements)
references
References 39 publications
25
929
3
7
Order By: Relevance
“…It is quite possible that targeting only 1 inhibitory receptor will be insufficient to release the inhibition on NK cells in all tumors. Other checkpoint receptors may be dynamically upregulated in an adaptive fashion similar to T cell immune checkpoint adaptive resistance recently observed in lung adenocarcinoma (74). Therefore, targeting multiple receptors on the NK cell population may be particularly useful in head and neck cancer.…”
Section: Discussionmentioning
confidence: 90%
“…It is quite possible that targeting only 1 inhibitory receptor will be insufficient to release the inhibition on NK cells in all tumors. Other checkpoint receptors may be dynamically upregulated in an adaptive fashion similar to T cell immune checkpoint adaptive resistance recently observed in lung adenocarcinoma (74). Therefore, targeting multiple receptors on the NK cell population may be particularly useful in head and neck cancer.…”
Section: Discussionmentioning
confidence: 90%
“…For instance, a recent preclinical study found T cells exploiting T-cell immunoglobulin mucin-3 (TIM3) to drive lung cancer growth despite anti-PD1 therapy. 42 Thus, future studies will have to concentrate on delineating such alternative GBM-associated immune checkpoints to design more tumor-specific ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…25 Therefore, this study examines the efficacy and mechanism of dual anti-PD-1 and anti-TIGIT checkpoint blockade in a murine glioma model. We hypothesized that combination therapy leads to a significant increase in survival via modulations of both the T cell and myeloid compartments of the immune system.…”
Section: Introductionmentioning
confidence: 99%